High-temperature-resistant special high-strength sulphoaluminate cement as well as preparation process and application thereof

By using low-grade solid waste to prepare sulfaluminate cement clinker containing Q phase and calcium aluminate mineral phase, the problems of high cost, shortage of raw materials and insufficient high temperature resistance are solved, and high strength and high temperature resistance are improved.

CN119504161APending Publication Date: 2025-02-25UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721704.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional Bailite sulfa aluminate cement has problems such as high costs, shortage of raw materials, insufficient compressive strength growth in the later stage, insufficient high temperature resistance and excessive hydration heat.

Method used

New sulfur aluminate cement clinker containing Q phase and calcium aluminate mineral phase is prepared by using low-grade solid waste such as high-magnesium limestone and low-grade bauxite instead of high-quality raw materials through specific calcining and grinding processes.

Benefits of technology

It has achieved the reduction of production costs, improved the high temperature resistance and later compressive strength of cement clinker, prevented the conversion of the Bellite phase into poor crystalline γ-C2S, and improved the chemical stability and thermal shock resistance of cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses high-temperature-resistant special high-strength sulphoaluminate cement as well as a preparation process and application thereof. The mineral phase of the cement clinker comprises the following components in percentage by weight: 10.56%-15.21% of calcium sulphoaluminate (C4A3), 17.40%-26.45% of alpha-dicalcium silicate (alpha-C2S), 5.11%-9.67% of beta-C2S, 15.75%-25.66% of a Q phase, 22.61%-34.88% of calcium aluminate (CA), 4.33%-8.50% of calcium aluminoferrite (C4AF) and the balance of unavoidable impurity phases. The raw materials of the cement clinker are also doped with a modifier, and the modifier simultaneously comprises a metal oxide and a non-metal substance. The novel high-temperature-resistant sulphoaluminate cement is prepared by replacing high-quality raw materials with low-grade solid wastes, and the problems that the compressive strength increase in the later period is insufficient and the belite phase is easily converted to poor crystal form gamma-C2S are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement clinker preparation, and in particular to a high-temperature resistant special high-strength sulphoaluminate cement and a preparation process and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] In recent years, as the global call for energy conservation and emission reduction has become louder and louder, my country, as a major cement producer, has also faced huge challenges. Data show that the global cement production in 2021 was 4.31 billion tons, of which China's production was 2.36 billion tons, accounting for about 55%. The huge production and application demand for cement has led to the increasing scarcity of limestone resources (especially high-grade limestone) in my country. Therefore, solid wastes including high-magnesium limestone and low-grade bauxite have gradually come into people's view and become new calcium resources and are used.

[0004] Belite sulphoaluminate cement is a hydraulic cementitious material with anhydrous calcium sulphoaluminate and dicalcium silicate as the main mineral components. Compared with ordinary Portland cement, it has the characteristics of high strength, high frost resistance, high impermeability, and low alkalinity. However, traditional Belite sulphoaluminate cement has the following shortcomings: (1) Currently, high-quality raw materials are used to burn this cement, which faces the problems of high cost and gradual shortage of raw materials. (2) The compressive strength develops slowly in the later stage and may even shrink. This is because in the later stage of hydration, the hydration products will change from metastable CAH 10 and C2AH8 to stable C3AH6. This transformation leads to an increase in relative density, an increase in porosity, and an unstable structure, which in turn causes a reduction in strength. (3) Insufficient high temperature resistance limits the use of this cement under high temperature conditions (such as high temperature kilns, chimneys, furnaces and other refractory structures). This is because the main product of sulfoaluminate cement, calcium sulfonate (AFt), decomposes into calcium sulfonate (AFm) with lower strength at high temperatures. (4) Due to the high content of calcium sulfoaluminate in this type of cement, a large amount of hydration heat is released in a short period of time during the hydration reaction, which causes deformation and cracking of the concrete, reducing the strength and durability of the prepared cement product. (5) During the cooling process of this cement clinker after calcination, the belite phase in it is easily converted into low hydration activity γ-C2S due to insufficient cooling rate, resulting in a decrease in the strength of the prepared cement product. Summary of the invention

[0005] In view of the above problems, the present invention provides a high-temperature resistant special high-strength sulphoaluminate cement and its preparation process and application, which uses low-grade solid waste instead of high-quality raw materials to prepare a new type of high-temperature resistant sulphoaluminate cement, and overcomes the problems of insufficient growth of late compressive strength and preventing the belite phase from easily transforming into the undesirable crystalline form γ-C2S. Specifically, the present invention discloses the technical solution as shown below.

[0006] Firstly, the present invention discloses a high-temperature resistant special high-strength sulphoaluminate cement raw material, which comprises the following components: 53.55-58.84% of high-magnesium limestone, 31.77-41.31% of low-grade bauxite, 0.43-4.74% of antimony slag, 1.91-2.63% of steel slag, and 2.1-2.61% of desulfurized gypsum.

[0007] Furthermore, the high-magnesium limestone refers to limestone containing magnesium. Optionally, the high-magnesium limestone has a magnesium content of 5-7.1%.

[0008] Furthermore, the low-grade bauxite includes at least one of grade V bauxite, grade VI bauxite, etc.

[0009] Secondly, the present invention discloses a high-temperature resistant special high-strength sulphoaluminate cement clinker, comprising the following mineral phase components: calcium sulphoaluminate (C4A3$) 10.56~15.21%, α-dicalcium silicate (α-C2S) 17.4~26.45%, β-C2S 5.11~9.67%, Q phase 15.75~25.66%, calcium aluminate (CA) 22.61~34.88%, calcium aluminoferrite (C4AF) 4.33~8.50%, and the remainder is inevitable impurity phase.

[0010] Again, the present invention discloses a method for preparing the high-temperature resistant special high-strength sulphoaluminate cement clinker, comprising the steps of: uniformly mixing the components in the cement raw material with water to form a raw material cake, and then calcining it, and after completion, rapidly cooling the calcined product to room temperature, and grinding it to obtain the cement clinker.

[0011] Furthermore, the mass ratio of each component to water is 1:0.3~0.35.

[0012] Furthermore, the calcination temperature is 1300-1350° C., and the calcination time is 60-90 min.

[0013] Furthermore, the fineness of the cement clinker is 200-300 mesh.

[0014] Finally, the present invention discloses the application of the high-temperature resistant special high-strength sulphoaluminate cement clinker in high-temperature industrial fields such as kilns, steel smelting, glass production, furnace bodies, etc.

[0015] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: The present invention uses industrial solid wastes such as high-magnesium limestone, low-grade bauxite, antimony slag, steel slag tailings, and desulfurized gypsum as raw materials to prepare all-solid waste-based sulphoaluminate cement raw materials, which not only realizes the utilization of these solid wastes, but also overcomes the dependence on high-quality raw materials, thereby reducing production costs and reducing many problems caused by mining high-quality raw materials. In addition, the present invention also uses the cooperation between these raw materials to form a new cement clinker system containing Q phase and calcium aluminate mineral phase in the prepared cement clinker, effectively overcoming the problems of insufficient late compressive strength growth of traditional sulphoaluminate cement and easy conversion of belite phase to poor crystalline form γ-C2S. At the same time, the cement clinker of the present invention also has excellent high temperature resistance, so that it can be stably used in special working conditions such as high temperature. The reason is that: (1) The present invention uses the characteristics of magnesium element contained in high-magnesium limestone, a low-grade raw material, to introduce Q phase into the cement clinker of the present invention. The late hydration rate of this mineral phase is higher than that of C2S, so that more hydration and gelling products can be formed, promoting the late compressive strength development of cement and preventing the phenomenon of strength shrinkage. In addition, the Q phase also improves the chemical stability of cement clinker, helps to reduce the pulverization of cement clinker during storage and use, thereby reducing the strength of clinker. (2) The calcium aluminate introduced into the prepared sulphoaluminate cement clinker system of the present invention has the effect of promoting the cooling rate of the calcined cement clinker, thereby preventing the problem of the conversion of the belite phase to the poor crystalline form γ-C2S due to insufficient cooling rate, and achieving the effect of activating the belite phase and improving the stability of the belite phase. (3) When the calcium aluminate is heated to 300-400°C, the strength decreases, but the residual strength no longer decreases thereafter. When heated to a high temperature of 1100°C, the structural water is completely released, and then sintered with the calcium aluminum compound in the hydration product of the Q phase to react with the high temperature solid phase to form a stable high temperature and high strength phase, thereby significantly improving the strength of the material again. At the same time, the calcium aluminate can also maintain good volume stability under high temperature environment, is not prone to thermal expansion or contraction, and avoids the generation of cracks caused by this. In addition, the calcium aluminate has a strong thermal shock resistance, which allows the concrete product prepared from the sulphoaluminate cement clinker of the present invention to withstand rapid temperature changes without cracking, and because of its good resistance to chemical erosion at high temperatures, it remains stable in a high-temperature environment with active chemical properties, reducing the accelerated chemical corrosion caused by the high-temperature environment. As a result, the concrete product prepared from the sulphoaluminate cement clinker of the present invention still maintains a high strength at a high temperature of 1300-1400°C, which is a significant improvement compared to the traditional sulphoaluminate cement that can only withstand a temperature of 400°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0017] Figure 1 This is a sample picture of the high temperature resistant special high strength sulphoaluminate cement clinker prepared in the following Example 1.

[0018] Figure 2 The XRD spectrum of the high temperature resistant special high strength sulphoaluminate cement clinker prepared in the following Example 1.

[0019] Figure 3 This is a sample picture of the high temperature resistant special high strength sulphoaluminate cement clinker prepared in the following Example 2.

[0020] Figure 4 The XRD spectrum of the high temperature resistant special high strength sulphoaluminate cement clinker prepared in the following Example 2.

[0021] Figure 5 This is a sample picture of the high-temperature resistant special high-strength sulphoaluminate cement clinker prepared in the following Example 3.

[0022] Figure 6 The XRD spectrum of the high temperature resistant special high strength sulphoaluminate cement clinker prepared in the following Example 3. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0024] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0025] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0026] In the following examples, the high-magnesium limestone, low-grade bauxite, antimony slag, steel slag tailings, and desulfurized gypsum are from Hunan Shaofeng Cement.

[0027] Example 1 A method for preparing high-temperature resistant special high-strength sulphoaluminate cement clinker comprises the following steps: (1) Weigh the following raw materials: 58.84% high-magnesium limestone, 31.77% low-grade bauxite, 4.74% antimony slag, 2.55% desulfurized gypsum, and 2.1% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0028] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.3 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0029] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first heated to 1000°C at a rate of 10°C / min, then heated to 1300°C at a rate of 5°C / min and kept warm for 90 minutes. After completion, the calcined product is taken out and quenched with a fan. After completion, a clinker block is obtained. After grinding it in a ball mill and passing it through a 200-mesh sieve, cement clinker is obtained. Figure 1 shown.

[0030] 1. The mineral components of the cement clinker prepared in this embodiment were tested, and the results were as follows: Figure 2 Among them, the content of calcium sulfoaluminate (C4A3$) is 10.56%, the content of α'-dicalcium silicate (α'-C2S) is 26.45%, the content of β-C2S is 9.67%, the content of Q phase is 15.75%, the content of calcium aluminate (CA) is 30.25%, the content of calcium aluminoferrite (C4AF) is 4.33%, and the rest is inevitable impurities.

[0031] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0032] Example 2 (1) Weigh the following raw materials: 54.36% high-magnesium limestone, 40.27% low-grade bauxite, 0.85% antimony slag, 1.91% desulfurized gypsum, and 2.61% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0033] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.35 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0034] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first heated to 1000°C at a rate of 10°C / min, then heated to 1320°C at a rate of 5°C / min and kept warm for 75 minutes. After completion, the calcined product is taken out and quenched by blowing with a fan. After completion, a clinker block is obtained. After grinding it in a ball mill and passing it through a 300-mesh sieve, cement clinker is obtained. Figure 3 shown.

[0035] 1. The mineral components of the cement clinker prepared in this embodiment were tested, and the results were as follows: Figure 4 Among them, the content of calcium sulfoaluminate (C4A3$) is 12.41%, the content of α-dicalcium silicate (α-C2S) is 17.40%, the content of β-C2S is 5.11%, the content of Q phase is 19.36%, the content of calcium aluminate (CA) is 34.88%, the content of calcium aluminoferrite (C4AF) is 6.86%, and the rest is inevitable impurities.

[0036] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0037] Example 3 (1) Weigh the following raw materials: 53.55% high-magnesium limestone, 41.31% low-grade bauxite, 0.43% antimony slag, 2.63% desulfurized gypsum, and 2.1% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0038] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.32 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0039] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first heated to 1000°C at a rate of 10°C / min, then heated to 1350°C at a rate of 5°C / min and kept warm for 60 minutes. After completion, the calcined product is taken out and quenched by blowing with a fan. After completion, a clinker block is obtained. After grinding it in a ball mill and passing it through a 200-mesh sieve, cement clinker is obtained. Figure 5 shown.

[0040] 1. The mineral components of the cement clinker prepared in this embodiment were tested, and the results were as follows: Figure 6 Among them, the content of calcium sulfoaluminate (C4A3$) is 15.21%, the content of α'-dicalcium silicate (α'-C2S) is 20.61%, the content of β-C2S is 5.78%, the content of Q phase is 25.66%, the content of calcium aluminate (CA) is 22.61%, the content of calcium aluminoferrite (C4AF) is 8.50%, and the rest is inevitable impurities.

[0041] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0042] Example 4 A method for preparing high-temperature resistant special high-strength sulphoaluminate cement clinker comprises the following steps: (1) Weigh the following raw materials: 62.25% limestone, 26.65% low-grade bauxite, 3.74% antimony slag, 3.55% desulfurized gypsum, and 3.81% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0043] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.3 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0044] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first raised to 1000°C at a rate of 10°C / min, then raised to 1300°C at a rate of 5°C / min and kept warm for 90 minutes. After completion, the calcined product is taken out and quenched with a fan. After completion, a clinker block is obtained. It is placed in a ball mill and ground through a 200-mesh sieve to obtain cement clinker.

[0045] 1. The mineral phase components of the cement clinker prepared in this embodiment were tested, wherein: the content of calcium sulfoaluminate (C4A3$) was 20.66%, the content of α'-dicalcium silicate (α'-C2S) was 30.56%, the content of β-C2S was 11.67%, the content of calcium aluminate (CA) was 28.88%, the content of calcium aluminate iron (C4AF) was 5.61%, and the remainder was inevitable impurities.

[0046] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0047] Example 5 A method for preparing sulphoaluminate cement clinker comprises the following steps: (1) Weigh the following raw materials: 63.36% high-magnesium limestone, 30.27% low-grade bauxite, 2.85% antimony slag, 1.91% desulfurized gypsum, and 1.61% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0048] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.35 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0049] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first heated to 1000°C at a rate of 10°C / min, then heated to 1320°C at a rate of 5°C / min and kept warm for 75 minutes. After completion, the calcined product is taken out and quenched with a fan. After completion, a clinker block is obtained. The clinker is placed in a ball mill and ground through a 300-mesh sieve to obtain cement clinker.

[0050] 1. The mineral phase components of the cement clinker prepared in this embodiment were tested, wherein: the content of calcium sulfoaluminate (C4A3$) was 20.41%, the content of α'-dicalcium silicate (α'-C2S) was 20.38%, the content of β-C2S was 9.26%, the content of γ-C2S was 7.24%, the content of Q phase was 33.56%, the content of calcium aluminoferrite (C4AF) was 5.66%, and the remainder was inevitable impurities.

[0051] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0052] Example 6 A method for preparing sulphoaluminate cement clinker comprises the following steps: (1) Weigh the following raw materials: 73.55% limestone, 20.31% low-grade bauxite, 1.55% antimony slag, 2.61% desulfurized gypsum, and 1.98% steel slag tailings. The low-grade bauxite is Grade VI bauxite, and its Al2O3 content is 57.15%.

[0053] (2) Add the above raw materials to a ball mill and grind them to a fineness of ≤75μm. Mix the obtained mixture with water in a mass ratio of 1:0.32 and stir evenly. Place the obtained wet material in a mold to form a cylinder with a diameter of 10mm and a height of 15mm, and then place it in an oven and dry it at 100℃ for 5 hours to obtain a raw cake.

[0054] (3) The raw material cake is placed in a silicon carbon rod electric furnace, first raised to 1000°C at a rate of 10°C / min, then raised to 1350°C at a rate of 5°C / min and kept warm for 60 minutes. After completion, the calcined product is taken out and quenched with a fan. After completion, a clinker block is obtained. It is placed in a ball mill and ground through a 200-mesh sieve to obtain cement clinker.

[0055] 1. The mineral phase components of the cement clinker prepared in this embodiment were tested, wherein: the content of calcium sulfoaluminate (C4A3$) was 30.65%, the content of α'-dicalcium silicate (α'-C2S) was 17.66%, the content of β-C2S was 27.26%, the content of γ-C2S was 13.29%, the content of calcium aluminoferrate (C4AF) was 8.50%, and the remainder was inevitable impurities.

[0056] 2. The late (28d) compressive strength and high temperature resistance of the cement clinker prepared in this embodiment are tested. Among them: the calcined clinker is mixed with dihydrate gypsum to obtain a mixed powder (wherein the dihydrate gypsum content is 15wt.%), and the test method for the high temperature resistance is to place the test block cured for 28 days in a high-temperature furnace and calcine at 500°C and 1400°C for 30 minutes, respectively, and then conduct a compressive strength test. The above compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), and the results are shown in the following table: .

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high temperature resistant special high strength sulphoaluminate cement raw material, characterized in that: It includes the following components: high-magnesium limestone 53.55~58.84%, low-grade bauxite 31.77~41.31%, antimony slag 0.43~4.74%, steel slag 1.91~2.63%, and desulfurization gypsum 2.10~2.61%.

2. The high temperature resistant special high strength sulphoaluminate cement raw material according to claim 1, characterized in that: The high-magnesium limestone refers to limestone containing magnesium.

3. The high temperature resistant special high strength sulphoaluminate cement raw material according to claim 2, characterized in that: The high-magnesium limestone has a magnesium content of 5-7.1%.

4. The high temperature resistant special high strength sulphoaluminate cement raw material according to any one of claims 1 to 3, characterized in that: The low-grade bauxite includes at least one of grade V bauxite and grade VI bauxite.

5. A high temperature resistant special high strength sulphoaluminate cement clinker, characterized in that: The mineral phase components include: calcium sulfoaluminate 10.56~15.21%, α-C2S 17.40~26.45%, β-C2S 5.11~9.67%, Q phase 15.75~25.66%, calcium aluminate 22.61~34.88%, calcium ferroaluminate 4.33~8.50%, and the remainder is inevitable impurities.

6. The method for preparing the high temperature resistant special high strength sulphoaluminate cement clinker according to claim 5, characterized in that: The method comprises the following steps: uniformly mixing the components in the cement raw material according to any one of claims 1 to 4 with water to form a raw material cake, and then calcining the raw material cake; after the calcination, rapidly cooling the calcined product to room temperature, and grinding the raw material cake to obtain the cement clinker.

7. The method for preparing high temperature resistant special high strength sulphoaluminate cement clinker according to claim 6, characterized in that: The mass ratio of each component to water is 1:0.3~0.

35.

8. The method for preparing high temperature resistant special high strength sulphoaluminate cement clinker according to claim 6, characterized in that: The calcination temperature is 1300-1350° C. and the calcination time is 60-90 minutes.

9. The method for preparing high temperature resistant special high strength sulphoaluminate cement clinker according to any one of claims 6 to 8, characterized in that: The fineness of the cement clinker is 200-300 meshes.

10. Use of the high temperature resistant special high strength sulphoaluminate cement clinker according to claim 5 or the cement clinker obtained by the preparation method according to any one of claims 6 to 8 in kilns, steel smelting, glass production or furnace bodies.